2003
DOI: 10.1074/jbc.m304930200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Target Genes of the p16INK4A-pRB-E2F Pathway

Abstract: Deregulation of the retinoblastoma protein (pRB) pathway is a hallmark of human cancer. The core members of this pathway include the tumor suppressor protein, pRB, which through binding to a number of cellular proteins, most notably members of the E2F transcription factor family, regulates progression through the cell division cycle. With the aim of identifying transcriptional changes provoked by deregulation of the pRB pathway, we have used cell lines that conditionally express a constitutively active phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
96
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(114 citation statements)
references
References 68 publications
(79 reference statements)
12
96
1
4
Order By: Relevance
“…Using a global testing approach, a significant enrichment of genes regulated by the p16inka/pRb/E2F pathway in U-2 OS cells 28 as well as those containing E2F binding sites 29 was observed in DLBCL 9p21del cases ( Figure 6A). These sets of genes were highly expressed in DLBCL 9p21del , indicating that the GEP of DLBCL 9p21del is at least partially related to the loss of RB1 regulation and to the release of its downstream targets.…”
Section: Biologic Pathways Involved In the Dlbcl 9p21del Subgroupmentioning
confidence: 99%
“…Using a global testing approach, a significant enrichment of genes regulated by the p16inka/pRb/E2F pathway in U-2 OS cells 28 as well as those containing E2F binding sites 29 was observed in DLBCL 9p21del cases ( Figure 6A). These sets of genes were highly expressed in DLBCL 9p21del , indicating that the GEP of DLBCL 9p21del is at least partially related to the loss of RB1 regulation and to the release of its downstream targets.…”
Section: Biologic Pathways Involved In the Dlbcl 9p21del Subgroupmentioning
confidence: 99%
“…VRK1 expression is also activated by E2F and inhibited by p16 and nonphosphorylated retinoblastoma (Rb; ref. 21). VRK1 has a serine/threonine kinase activity and phosphorylates several transcription factors, including human p53 (22), and can also cooperate with the c-Jun NH 2 -terminal kinase pathway by phosphorylation of c-Jun (23) and ATF2 (24).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we investigated expression profiling of genes selectively regulated by either CDKN2A (p16) or by E2F as reported by Vernell et al (2003). We found that hierarchical clustering based on CDKN2A (p16)-regulated genes could not reproduce the unsupervised clustering (Figure 3Ca), while genes regulated directly by E2F reproduced the unsupervised cluster analysis (Figure 3Cb).…”
Section: Mcm7mentioning
confidence: 70%
“…However, the effect of high-risk HPV on global gene expression has been studied and characterised in several model systems on different microarray platforms (Chang and Laimins, 2000;Nees et al, 2001;Alazawi et al, 2002;Vernell et al, 2003;Garner-Hamrick et al, 2004;Loercher et al, 2004;Santin et al, 2005). Several biomarkers predicting both HPV status and response to treatment for several cancers have been proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation